Pharmacokinetic profiles of Moutan Cortex after single and repeated administration in a dinitrobenzene sulfonic acid-induced colitis model - Jin-Hwa Kim; Ji-Soo Jeong; Jeong-Won Kim; Eun-Hye Chung; Su-Ha Lee; Je-Won Ko; Youn-Hwan Hwang; Tae-Won Kim (PLoS ONE, 2025)
Moutan Cortex (MC), the dried root bark of Paeonia suffruticosa , is used in traditional Chinese and Korean medicine to treat enteritis for its anti-inflammatory properties. This study compared the pharmacokinetic (PK) profiles of paeonol and paeoniflorin in normal and dinitrobenzene sulfonic acid (DNBS)-induced colitis rats, and to determine how repeated low-dose MC [MC(L), 0.5 g/kg] or high-dose MC [MC(H), 2.5 g/kg] alters PK and disease severity. Using ultra-performance liquid chromatography–tandem mass spectrometry, we found that DNBS modestly increased paeonol AUC last (NC: 247.8 ± 63.7 vs DNBS: 337.0 ± 120.8 hr*ng/mL) and decreased paeoniflorin (NC: 474.1 ± 11.7 vs DNBS: 463.7 ± 106.8 hr*ng/mL) compared to controls (ns). After repeated dosing, the maximum plasma concentration (C max ) of paeonol was higher in the MC(H) than that in the MC(L) group (MC(L): 63.81 ± 29.74 vs MC(H): 4221.5 ± 1579.2 ng/mL, p < 0.05). Paeoniflorin C max in the MC(H) group was also higher than MC(L) group (MC(L): 60.5 ± 15.3 vs MC(H): 164.7 ± 74.7 ng/mL, p < 0.05). Repeated MC(H) treatments improved body weight loss and disease activity index. Western blots indicated that the expression of intestinal epithelial integrity-related proteins in the MC(H) group was comparable to that in the control. Inflammation did not influence paeonol and paeoniflorin PK significantly, whereas MC(H) group markedly increased systemic exposure, especially of paeonol, and demonstrated symptom relief. Appropriate dose adjustments are necessary to ensure safe and effective therapy because PK changes can lead to increased systemic exposure and affect treatment outcomes.